Unmasking Hepatitis C Infection: A Case Report of Interstitial Lung Disease as a Potential Extrahepatic Manifestation - Zeina Morcos; Chloe Lahoud; Waleed Azam; Mark Tawfik; Yisroel Grabie; Sudeep Acharya; Thomas Kilkenny (Journal of Advanced Lung Health, 2025)
Hepatitis C virus (HCV) is the most common blood-borne infection in the United States and is a significant public health concern worldwide. There is a potential association between HCV infection and the development of interstitial lung disease (ILD) as an extrahepatic manifestation. This report details the case of a 77-year-old female who presented with a chronic productive cough and chest discomfort, initially suspected to be indicative of atypical pneumonia. Despite an initial course of antibiotics, her symptoms persisted, leading to further investigations. Imaging revealed features consistent with ILD prompting additional testing. The patient was noted to have positive results for hepatitis C antibodies and antinuclear antibodies (ANAs), alongside evidence of minimal liver fibrosis. She received 12-week course of antivirals sofosbuvir-velpatasvir for the treatment of hepatitis C infection. Several studies published in the literature have reported a high incidence of HCV infection among patients with ILD. Although definitive clinical and pathological causality remains elusive, the case presented and the literature reviewed strongly suggest a possible role of HCV infection in the onset of ILD. Further research is needed to provide early diagnosis, develop targeted therapeutic strategies, and improve patient outcomes.